National Digital Transformation as an Instrument in Accelerating the Leadership Transformation of Indonesia's Young Generation - Sutiono, Pribadi; Roedyati, Joevi (Jurnal Locus Penelitian dan Pengabdian, 2026)
The rapid evolution of technology and the ongoing digital transformation are fundamentally reshaping the nature of leadership, particularly for the younger generation in emerging economies like Indonesia. This creates an urgent need to understand the competencies required for future leaders to navigate this new landscape effectively. This study investigates the leadership styles of Indonesia's future young generation, focusing on identifying the defining characteristics of effective leadership in a digitally accelerated era. Using a qualitative research approach, the study employed semi-structured interviews with emerging leaders from diverse sectors such as business, education, technology, and social activism. Thematic analysis of the data revealed key leadership traits, including adaptability, digital fluency, collaborative orientation, and a strong sense of ethical and inclusive practice. The findings highlight that effective future leadership is not only about individual skills but is also deeply intertwined with the broader national digital ecosystem, including infrastructure and supportive policies. The study concludes that fostering these competencies through integrated educational, training, and policy initiatives is essential for developing a generation of leaders capable of driving sustainable innovation and inclusive growth in Indonesia's digital future.